DISPLACEMENTS IN THE GLOBAL EDUCATIONAL SPACE IN MODERN CONDITIONS (REGIONAL AND NATIONAL DIMENSIONS) - Zaykovskyi , O.S. (The actual problems of regional economy development, 2020)
The article is devoted to the study of modern global processes that significantly affect the transformation of the higher education system. Internationalization has become not only an integral part of the continuous process of change in higher education, in fact, the processes of internationalization of higher education have become an important determinant of the development and reform of higher education. In the context of global transformations of the modern world, international cooperation has become an important indicator of educational development, and universities themselves are becoming global institutions, whose influence on the formation of competitive advantages of the national socio-economic system is constantly increasing. As the internationalization of higher education radically changes the place and role of universities, there is a need to study and identify relevant trends that take into account the transformations taking place at the national, regional and global levels and determined the purpose of the scientific article. To achieve this goal, general and special research methods were used, namely: methods of analysis, abstraction and synthesis (in the study of trends that take into account both internal transformations and global changes, and which determine the development of higher education); methods of classification and system generalization (for systematization of structural transformations occurring in educational services); statistical methods (to quantify the transformations taking place in the global educational space in modern conditions). It is proved that taking into account the changes taking place in higher education involves the expanded development of international research and educational programs and projects, the creation of an extensive network between university cooperation while taking into account and preserving the best national traditions and cultural values.